Abundance tomography of type Iax SN 2011ay with tardis - Barna, Barnabás; Kromer, Markus (Monthly notices of the Royal Astronomical Society, 2017)
Abstract. We present a detailed spectral analysis of Type Iax SN 2011ay. Our spectra cover epochs between −3 and +19 d with respect to the maximum light in B b
Gesehen am 24.09.2018